Analisis Rasio Likuiditas, Solvabilitas, Dan Profitabilitas Dalam Mengukur Kinerja Keuangan Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Bursa Efek Indonesia - A. Febby Lestari; Nurlina Nurlina; A. Tenri Syahriani (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The purpose of this study is a type of quantitative research aimed at analyzing Liquidity, Solvency, and Profitability Ratios to assess the financial performance of food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The sample in this Study consist of 22 companies selected is secondary data. Data collection was carried out using the documentation method, including the annual financial reports of food and beverage sector companies listed on Indonesia Stock Exchange. Based on the results, the Liquidity Ratio measured using the Current Ratio, Quick Ratio, and Cash Ratio indicates that food and beverage sector companies during the 2019-2023 period were in a “good” condition. Meanwhile, the Solvency Ratio, measured by the Debt to Asset Ratio and Debt to Equity Ratio, was in a “less favorable” condition. Furthermore, the Profitability Ratio measured through Net Profit Margin, Return on Asset, and Return on Equity also showed a “less favorable” condition. This reflects that the companies’ ability to generate profit and manage debt still needs improvement